P1-S5.25 Acyclovir and transmission of HSV-2 from HSV-2/HIV-1 dually infected persons. (10th July 2011) - Mujugira, A; Margaret, A; Celum, C; Lingappa, J; Baeten, J; Fife, K; De Bruyn, G; Bukusi, E; Corey, L; Wald, A
Abstract : Background: Daily suppressive therapy with valacyclovir reduces the risk of sexual transmission of HSV-2 in healthy HSV-2 serodiscordant heterosexual couples by 48%. Whether suppressive therapy reduces HSV-2 transmission from persons who have both HIV-1 and HSV-2 is unknown. Methods: Within a randomised trial of daily acyclovir 400 mg bid in African HIV-1 serodiscordant couples, in which the HIV-1 infected partner was HSV-2 seropositive, we identified partnerships in which the HIV-1 susceptible partners were HSV-2 seronegative. Cox proportional hazards analysis was used. Results: We followed 911 HIV-1 and HSV-2 serodiscordant couples for a median of 18 months (IQR 3, 24). For 112 couples (12%), the HIV-1/HSV-2 infected partner was male, of whom 37% (34/91) were circumcised. 68 HSV-2 seroconversions were observed (an incidence of 5.1 per 100 person-years): 40 in the acyclovir group and 28 in the placebo group (HR 1.4, 95% CI 0.8 to 2.2; p=0.2). In a multivariate analysis of HSV-2 susceptible women, hormonal contraception (HR 3.84, 95% CI 1.32 to 11.14, p=0.013) and having an uncircumcised male partner (HR 8.91, 95% CI 1.17 to 67.85, p=0.035) were significant risk factors for HSV-2 acquisition. Among HSV-2 susceptible men, younger age was the only significant HSV-2 risk factor (p=0.014). Conclusions: Suppressive acyclovir therapy did not decrease the risk of HSV-2 transmission within HSV-2-serodiscordant couples in which the HSV-2-seropositive partner also had HIV-1 infection. Hormonal contraceptive use and lack of male circumcision in the HIV-1/HSV-2 dually infected male partners increased the risk of HSV-2 acquisition among initially HSV-2 seronegative women.